Exploring cannabinoid modulation on autophagy mechanisms in Alzheimer’s disease: a review - Ntsapi, C.; Weyers, M.; Chinheya, R.; Jim, T.; Matsabisa, M. (Frontiers in Pharmacology, 2026)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by the accumulation of toxic protein aggregates in the brain, leading to brain cell death and cognitive impairment. Central to AD pathogenesis is the autophagy pathway, a crucial cellular self-digestion process. Cannabinoids, the fundamental phytochemical compounds derived from the Cannabis sativa plant, have been demonstrated to exhibit neuroprotective qualities when used as a treatment at microdoses. However, the impact of multi-cannabinoid treatments on autophagy induction and subsequent cell survival in AD in vitro models remains uncertain. This review seeks to explore the potential of a multi-cannabinoid treatment strategy in enhancing neuronal cell survival through autophagy activation within an AD in vitro model. The proposed approach involves a combination of cannabinoids in their potential to upregulate autophagy mechanisms, potentially supporting neuronal cell resilience. By unravelling the mechanistic link between autophagy, cannabinoid treatment, and neuronal viability, this review aims to elucidate how cannabinoids influence neuronal function and survival at a cellular and molecular level. By offering insights into the exploitation of the endocannabinoid system, this review contributes to the development of novel cannabinoid-based treatment avenues for AD. This pursuit aligns with the broader objective of addressing the debilitating effects of AD on the quality of life for those affected.